Solar Azimuth Angle in the Tropical Zone (Journal of Solar Energy Research Updates, 2017)
Basing on the concept of sun position, appropriate relationships for determining the solar azimuth angle were derived. The derived formulas were compared with those available in literature and proposed to determine the solar azimuth angle all over the year and all over world. Some comments were given on some of them. Here it was found that the formulation of Braun and Mitchell [1], recommended by Duffie and Beckman [2] in their respectful book could not be applied in the tropical zone. The calculated results using the derived formulas were compared with the available results in literature.